ABOUT RESEARCH RESULTS OF MORPHOTECTONIC CONNECTIONS BETWEEN THE EARTH’S CRUST CRYSTALLINE FUNDAMENT, SEDIMENTARY LAYER AND MODERN RELIEF (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The results of author's recent years researches made by the complex of geophysical-geomorphological data and directed to the detection of morphotectonic connections between the Earth’s Crust deeper and surface structures are represented.
Keywords: Earth Crust crystalline fundament; Earth Crust sedimentary layer; modern relief; morphotectonic connections